KELOMPOK NON MEMBER GOLD'S GYM EXPRESS UNIVERSITAS INDONESIA: ANALISA MOTIVASI, KESADARAN, PENGETAHUAN PRODUK, DAN SIKAP KONSUMEN - , Fahmi Tarumanegara ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The slightly reaserch focuses on non-user groups in marketing or sport marketing studies, is contrasted with the fact that these group sometimes are the major part of business potential market. Although it is difficult to identify, examiation pshycological aspect of consumers, as a maker in purchase decission process, conceptually has relevance to used. This study examined the causality relationship between motivation, awareness, percieved quality, and product knowledge, to drive consumersâ intention in joining sport club or sport participation. A total 136 persons responded, and multinominal logistic regression was examined. The result shows those relationship exsist in, and each variable, except product knowledge, has its own influence to different type of consumersâ intention. Discussion of theoretical and practical issues is presented and directions for future research are suggested.